2016
DOI: 10.1016/j.neurad.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Absolute and regional cerebral perfusion assessment feasibility in head-down position with arterial spin-labeling magnetic resonance. A preliminary report on healthy subjects

Abstract: Regional CBF assessment, especially in HDT, is challenging with most perfusion techniques because of ionizing radiations, inherent limitations and logistical considerations. This preliminary report presents a noninvasive technique assessing regional and absolute cerebral blood flow changes in response to posture change. It can lead to further clinical investigations for a better understanding of cerebral perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Finally, our study was monocentric, which may limit the external validity of our results restricted to patients with large vessel proximal occlusion. These things being said, we believe our findings support the early benefit of TP and that they could motivate further studies in the aim to both increase "proof of concept" evidence [12] and investigate long-term functional outcomes [29]. In particular, we believe that the appropriate assessment of TP intervention safety is an indispensable prerequisite prior to a long-term evaluation of its effectiveness.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, our study was monocentric, which may limit the external validity of our results restricted to patients with large vessel proximal occlusion. These things being said, we believe our findings support the early benefit of TP and that they could motivate further studies in the aim to both increase "proof of concept" evidence [12] and investigate long-term functional outcomes [29]. In particular, we believe that the appropriate assessment of TP intervention safety is an indispensable prerequisite prior to a long-term evaluation of its effectiveness.…”
Section: Discussionsupporting
confidence: 63%
“…Very few studies have focused on HD positioning and they used NIRS or TCD, which provides only an indirect assessment of CBF or cerebral blood volume (CBV). Some studies assume that HD positioning or flat positioning increases CBF, while recent MR studies, measuring CBF indirectly through the phase‐contrast technique or through ASL, found a decrease. Two MRI technological advances enabled the design of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial spin‐labeling (ASL) is an MR perfusion technique providing images of regional CBF without contrast agent injection. In a previous study, the feasibility of using MR to directly assess CBF in the HD position was described …”
mentioning
confidence: 99%
“…There are many reports on the CBF and blood flow velocity in the HDT; however, the results of posture‐related blood flow analyses are inconsistent. It is difficult to interpret these previous reports due to diverse bias factors, eg, measured vessel location, procedure, tilt angle, and duration in the HDT . On the basis of our results, we speculate that the ICAs have a higher reactivity to posture changes than the VAs.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to interpret these previous reports due to diverse bias factors, eg, measured vessel location, procedure, tilt angle, and duration in the HDT. 13,[24][25][26] On the basis of our results, we speculate that the ICAs have a higher reactivity to posture changes than the VAs. Despite the significant increase in mean blood flow velocity of the ICAs, the tCBF was not significantly affected.…”
Section: Discussionmentioning
confidence: 99%